SIGNIFICANCE OF CHITOSAN TO IMPROVE THE SUBSTANTIVITY OF REACTIVE DYES - CHATHA,S. A. S (Sociedad Chilena de Química, 2016)
Chitosan (polysaccharide) is used for cationization of cotton and to increase the uptake of reactive dye by the cationized cotton. Four different concentration of chitosan (0.5, 1.0, 1.5 and 2.0%) were applied for 0.5 and 4.0% shades of C.I. Reactive Red and C.I. Reactive Yellow dye, respectively. Different properties e.g. K/S value, washing fastness, light fastness and rubbing fastness of the dyed cotton (untreated and treated with chitosan) were recorded for comparison. The K/S values of chitosan treated fabrics (6.1-13.9 and 18.3-22.8 for both dye shades, respectively) were considerably better than untreated fabric (4.7-5.3 and 16.8-17.0). The results of present study clearly demonstrated that the use of chitosan as an exhausting agent not only reduced the amount of dye for dyeing the cotton fabric but also improved the washing and rubbing fastness properties. The present study further demonstrated that the use of chitosan in textile industry can minimize the dyeing cost, effluent treatment cost and other auxiliary utilization.